Human Resource Information System Solusi Pelaksanaan Rekrutmen Digital untuk Mendukung Green Business - Anggraeni, Tiara (Applied Business and Administration Journal, 2022)
Year by year, the number of job applicants is increasing even in 2030 Indonesia is estimated to experience a demographic bonus so that the level of demand for job vacancies will be a matter of concern because of the high productive age group. This is closely related to the organization of recruitment, the company should be able to see the opportunities and threats that will come because of the high number of applicants. Currently, the recruitment system is one of the activities that incur the biggest costs of resource management schemes. In addition, the recruitment system by collecting the files of prospective applicants is also an environmental issue because with the traditional system, prospective applicants must submit their applications and become a pile of paper in the company and produce carbon during the transportation process for sending application files. Therefore, companies must start to become aware of and switch to a digital and automated resource management system so that applicants and HRD can share information easily with each other regarding recruitment and applicant data can be stored in one centralized system so that there are no more piles of paper or paperwork. carbon from file delivery transport. That way, the company's goals can be achieved effectively and efficiently. In addition, the higher goal is to be able to realize a green business to save the environment. The required human resource management system is called the Human resource information system. Seeing the importance of implementing digital recruitment to realize a green business, this research was prepared with the aim of knowing the process of the Human resource information system to be a solution in implementing digital recruitment so as to support the implementation of Green business. This study uses qualitative methods and literature review. The results show that the Human resource information system can be a digital solution for implementing digital recruitment to support Green business because the Human resource information system can be integrated and collect data centrally and is able to reduce paper waste and transportation carbon.